PERGESERAN PERILAKU WAMA-WAMA (STUDI ATAS PARA PENCARI SEDEKAH DI KECAMATAN BONANG DEMAK) - Mustaqim, Muhamad (IAIN Palangka Raya, 2020)
This study attempted to investigate the behavior of charity seekers in several villages in Bonang Demak sub-district. This study tried to compare the study that the author conducted seven years before, with wider object and focus of research. The study used a sociological and anthropological approach. The findings revealed that there was a shift in alms seeker behavior mode. First, the letter or proposal model has not been used anymore, although sporadically some still use this model. Second, the model of selling calendars was a model widely used, since it was more elegant. There were products sold like businesses, and minimize the prejudice of fraud as already existed. The model of selling calendars was actually the use of new packages of old content, namely exploiting religion for economic purposes. The implication was that the community did not need to hesitate if they did not want to give / to buy alms to the citizens.